What Remains after the Oil Boom Is Over? - Pavel Jelnov (Institute of Labor Economics (IZA), 2019)
This paper links between Beckerian literature that shows that marriage is a normal good with respect to male income and the literature that explores cultural changes as a result of exogenous events. I use the oil crisis of the 1970s as a positive shock on some males. The analyzed outcome is marital status at early twenties for women and at mid and late twenties for men. The probability to be never-married decreases in the American oil-producing areas immediately after the shock. This effect persists after the oil boom is over but longer for men than for women.
Keywords: J12; 330; oil; age of marriage